Identifying the variation of acid immersion and concrete cover on the crack width of reinforced concrete beams - Andardi, Faris Rizal; Soehardjono, Agoes; Wisnumurti, Wisnumurti; Wibowo, Ari (Eastern-European Journal of Enterprise Technologies, 2025)
This paper discusses the effect of acidic environments on concrete structures, particularly crack width. This study was conducted to investigate the effect of acid ph on crack width in reinforced concrete beams with different cover depths. Reinforced concrete beams were immersed in phosphoric acid (H3PO4) solution with a pH of 5.0 for 28 days using this technique. Three concrete cover thicknesses were tested: 20 mm, 30 mm, and 40 mm. The materials used include coarse aggregate, fine aggregate, cement and phosphoric acid solution. Crack width, concrete compressive strength and steel stress were measured while the two-span beams with different section shapes experiencing point loads. The findings demonstrated that exposure of concrete to an acidic environment led to a decrease in compressive strength between 15% and 40%, cracking becoming significant with the beams having thin layers, while these results range a crack width ranging from no visible cracks until cracks resulted opened up. Crack width is directly dependent upon the thickness of concrete, for thicker concrete layer reducing crack width. On the other hand, steel stress increases crack width, with more the steel stress greater is crack wider. This study is unique in that an empirical formula related to crack width can be used for the prediction and has a good agreement with experimental results. The results yield new understanding on the significance of controlling concrete cover depth and steel stress level in the design methodologies for reinforced-concrete structures to be more acid-resisting. These findings may have implications for the design of reinforced concrete structures that are more resistant to acidic environmental conditions